Impossible Subjects: Illegal Aliens and the Making of Modern America - - (Princeton University Press, 2014)
I began researching and writing about the origins of illegal immigration to the U.S. as a dissertation topic in the mid-1990s. I found those origins in the restrictive immigration laws that Congress legislated in the 1920s and the border-control measures implemented thereafter. Positive domestic law, not race, culture, or bad character, produced â€œillegal aliensâ€â€”an insight that would not be so novel but for pervasive stereotyping of Mexicans and other Latinos and Latinas in twentiethcentury American society. As I examined the history and contours of restriction, my thinking was influenced by recent scholarship on the historical nature of race and the nation, two categories of modern political life commonly thought to be natural and timeless. I believed that an analysis of the historical specificities of national and racial identities would offer new ways of thinking about immigration and citizenship. But if I was aware that I was pursuing a new line of inquiry, it is only in hindsight that I appreciate how much the greater intellectual terrain was shifting. Since the mid-1990s, the frameworks and methodologies guiding American immigration history have undergone a sea change. Impossible Subjects was influenced by, and helped constitute, that change. The multidisciplinary field of migration studies has been at the forefront of the â€œtransnational turnâ€ that has swept the humanities and social sciences. Human migration, along with the circulation of commodities, currencies, and information, highlights the phenomenon of â€œglobalization,â€ a multivalent concept referring generally to the interconnectedness of the world in our time (defined by communications technology, supranational organization, neoliberal market policy, etc.). In a related vein, scholars have historicized the nation, in Benedict Andersonâ€™s famous phrase, as an â€œimagined community.â€ With that insight also came recognition of nationalismâ€™s abiding influence on the practice of history. With much greater sensitivity to the construction of the American nation and the place of that nation in the world, scholars have critically reconceived immigration history in both domestic and global contexts. The normative assumptions that previously underlaid American immigration historyâ€”unidirectional migration, permanent settlement, and eventual inclusion, if not full assimilation and citizenshipâ€”have virtually collapsed in the face of alternate frameworks of analysis: transnationalism, diaspora, borderlands, colonialism and post-colonialism, hybridity. These concepts inform not only the study of contemporary immigration but also a reconsideration of earlier periods, reshaping historical analysis. By showing that national boundaries have always been porous and that migration patterns have always been diverse, these histories establish a critical position against nationalist history. They also serve as a corrective to the tendency among social scientists to treat globalization as a new phenomenon.